Hybrid Polydimethylsiloxane (PDMS) Incorporated Thermogelling System for Effective Liver Cancer Treatment - Panqin Ma; Lu Jiang; Xi Luo; Jiayun Chen; Qi Wang; Ying Chen; Enyi Ye; Xian Jun Loh; Caisheng Wu; Yun-Long Wu; Zibiao Li (Pharmaceutics, 2022)
For the delivery of anticancer drugs, an injectable in situ hydrogel with thermal responsiveness and prolonged drug release capabilities shows considerable potential. Here, we present a series of thermosensitive in situ hydrogels that serve as drug delivery systems for the treatment of liver cancer. These hydrogels were created by utilizing the polydimethylsiloxane (PDMS) oligomer, polyethylene glycol (PEG) and polypropylene glycol (PPG)’s chemical cross-linking capabilities. Doxorubicin (DOX) was encapsulated in a hydrogel with a hydrophobic core and hydrophilic shell to enhance DOX solubility. Studies into the behavior of in situ produced hydrogels at the microscopic and macroscopic levels revealed that the copolymer solution exhibits a progressive shift from sol to gel as the temperature rises. The hydrogels’ chemical composition, thermal properties, rheological characteristics, gelation period, and DOX release behavior were all reported. Subcutaneous injection in mice was used to confirm the injectability. Through the in vitro release of DOX in a PBS solution that mimics the tumor microenvironment, the hydrogel’s sustained drug release behavior was confirmed. Additionally, using human hepatocellular hepatoma, the anticancer efficacy of thermogel (DEP-2@DOX) was assessed (HepG2). The carrier polymer material DEP-2 was tested for cytotoxicity using HepG2 cells and its excellent cytocompatibility was confirmed. In conclusion, these thermally responsive injectable hydrogels are prominent potential candidates as drug delivery vehicles for the treatment of hepatocellular carcinoma.